METHODS OF DEVELOPING PEDAGOGICAL CREATIVITY OF FUTURE TEACHERS BASED ON A COMPETENT APPROACH - Bazarbaevna, Bekchonova Shoira; Azlar, Madjitova Kamola (Journal of Higher Education and Academic Advancement, 2024)
This article highlights the possibility of creating a solid foundation for the development of pedagogical creativity of future teachers by applying a competency-based approach to teacher education programs.